Twelve-month effects of everolimus on renal and lung function in lung transplantation: differences in chronic lung allograft dysfunction phenotypes. (February 2021) - Patrucco, Filippo; Allara, Elias; Boffini, Massimo; Rinaldi, Mauro; Costa, Cristina; Albera, Carlo; Solidoro, Paolo
Background: Chronic lung allograft dysfunction (CLAD), a complication affecting the survival of lung transplanted patients, includes two clinical phenotypes: bronchiolitis obliterans syndrome (BOS) and restrictive allograft syndrome (RAS). Everolimus is used in CLAD because of its antiproliferative mechanism. In lung transplant patients treated with everolimus, the clinical course of renal and lung function has not yet been assessed systematically in CLAD, BOS and RAS patients for more than 6 months. Methods: We retrospectively evaluated the 12-month follow-up of renal and lung function of lung-transplanted patients switched to everolimus and evaluated the reduction in immunosuppressant dosage (ISD) and mortality. Subgroups were based on indication for everolimus treatment: CLAD and non-CLAD patients, BOS and RAS among CLAD patients. Results: We included 26 patients, 17 with CLAD (10 BOS, seven RAS). After 1 year from the everolimus switch, we observed renal function improvement (serum creatinine −17%, estimated glomerular filtration rate +24%) and stable pulmonary function [forced expiratory volume in the first second (FEV1 ) −0.5%, forced vital capacity (FVC) +0.05%]. RAS patients had progressive functional loss, whereas BOS patients had FEV1 improvement and FVC stability. All-cause mortality was higher in the CLAD versus non-CLAD group (41% versus 11%), without differences between BOS and RAS patients ( p  > 0.05). All patients had significant and persistent ISD reduction. Conclusion: Lung transplant patients treated with everolimus had improvements in renal function and reduced ISD. We observed sustained improvements in lung function for CLAD related to BOS subgroup results, whereas RAS confirmed the 1-year worsening functional trend. Data seem to suggest one more piece of the puzzle in CLAD phenotyping.